Charge Correlations for Precise, Coulombically Driven Self Assembly. Issue 2 (17th November 2015) - Radhakrishna, Mithun; Sing, Charles E.
Abstract : Polyelectrolyte materials represent a challenge for polymer physicists, with a research literature that spans decades with little sign of slowing down. The essence of this challenge is how to treat charge correlations on both a theoretical as well as a conceptual basis. Charge correlations are related to the spatial arrangement of charges and can have a strong effect on the equilibrium state of polyelectrolyte systems. Accurate treatment of correlation effects is therefore integral to the design and development of materials consisting of (for example) charged gels, block copolymers, and biopolymers. In this Talents article, recent theoretical developments useful for understanding correlations are discussed. This understanding can shape the development of new materials, exposing new opportunities in precise, sequence‐based control over charge correlations in polymers and their emerging role in charge‐driven self‐assembly. Abstract : Polyelectrolyte materials are challenging to treat theoretically, in particular due to charge correlations. Charge correlations refer to the spatial arrangement of charges and profoundly dictate the equilibrium state of polyelectrolytes. This Talents & Trends article describes recent developments in the theory of correlated charges, and how correlations influence the self‐assembly of charged polymers. New opportunities in connectivity‐based materials design are discussed.